2019
DOI: 10.1002/ecy.2711
|View full text |Cite
|
Sign up to set email alerts
|

Integrating social and ecological data to model metapopulation dynamics in coupled human and natural systems

Abstract: Understanding how metapopulations persist in dynamic working landscapes requires assessing the behaviors of key actors that change patches as well as intrinsic factors driving turnover. Coupled human and natural systems (CHANS) research uses a multidisciplinary approach to identify the key actors, processes, and feedbacks that drive metapopulation and landscape dynamics. We describe a framework for modeling metapopulations in CHANS that integrates ecological and social data by coupling stochastic patch occupan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 58 publications
0
30
0
Order By: Relevance
“…, Van Schmidt et al. ). By integrating multiple sources of information into the modeling process, greater insights into environmental relationships and the mechanisms driving species distributions can occur.…”
Section: Discussionmentioning
confidence: 99%
“…, Van Schmidt et al. ). By integrating multiple sources of information into the modeling process, greater insights into environmental relationships and the mechanisms driving species distributions can occur.…”
Section: Discussionmentioning
confidence: 99%
“…Van Schmidt et al. () tackle the integration of social and ecological data via an agent‐based modeling approach to understand metapopulation dynamics in coupled human and natural systems (Fig. ).…”
mentioning
confidence: 99%
“…Van Schmidt et al. () combine five interdisciplinary data sets to model the metapopulation dynamics of the threatened Black Rail ( Laterallus jamaicensis ) in a coupled human and natural system, the irrigated rangelands of the foothills of California's Sierra Nevada. Their paper provides an example of integrating social and ecological data by coupling agent‐based models of land‐use change with a stochastic patch occupancy model of metapopulation dynamics.…”
mentioning
confidence: 99%
“…Season‐ and site‐specific probabilities were modeled as covariates via logit‐link functions. Our models included covariates that previous analyses identified as important predictors of rail metapopulation dynamics in this region (Richmond et al ; Van Schmidt et al ): sampling period‐specific detection probabilities, precipitation (mean over the past 120 days), and wetlands’ patch area, elevation (Geological Survey ), geomorphology and water sources (Appendix ).…”
Section: Methodsmentioning
confidence: 99%
“…Breeding season occupancy surveys of these metapopulations have been conducted annually for over a decade. Preliminary analyses of isolation–extinction relationships from 2002 to 2006 (Appendix ), a period with both metapopulations in dynamic equilibrium (Van Schmidt et al ), suggested the rescue effect was strong in black rails but not supported for Virginia rails (Fig. ).…”
Section: Introductionmentioning
confidence: 99%